Pharmacological Assessment, Green synthesis and Characterization of Silver Nanoparticles of Sonneratia apetala Buch.-Ham. Leaves - Peddinti Nagababu, Vanga Umamaheswara Rao (Journal of Applied Pharmaceutical Science, 2017)
The present investigation evaluates phytochemical screening, antibacterial, antioxidant activities and green synthesis, characterization of silver nanoparticles and its antibacterial activity. Three dissimilar solvents viz., hexane, ethyl acetate and methanol were used to prepare crude extracts of Sonneratia apetala leaves to study the phytochemicals, antibacterial and antioxidant activities. Green synthesis, characterization of silver nanoparticles (AgNPs) and its antibacterial activity using S. apetala leaves were also studied. Antioxidant activity was examined by means of DPPH free radical scavenging method. AgNPs were synthesized by using 1mM AgNO3 solution mixed with leaf aqueous extract of S. apetala. The characterization of the prepared AgNPs was done by UV-Vis spectrometry, FTIR spectroscopy and Scanning electron microscopy. Antibacterial activity was studied by agar well diffusion method. The phytochemical screening results unveiled the bearing of different phytochemicals viz., flavonoids, alkaloids, saponins, carbohydrates, terpenoids, steroids, tannins and free anthraquinones particularly with relatively high abundance in methanol extract. Likewise methanol extract too exhibited effective free radical scavenging and antibacterial activities. The characterization results of the prepared AgNPs displayed that the silver nanoparticles are formed and stabilized by plant phyto-constituents and also exhibited virtuous antibacterial property with great antagonism towards Proteus mirabilis with 27.3 mm diameter zone of inhibition. Green synthesis process is a pivotal area in nanotechnology and usage of natural resources is the best choice for the making of NPs as a sustainable, eco-friendly, inexpensive and free of chemical contaminant method. These AgNPs have several potential biological and medical applications.
Keywords: Sonneratia apetala, Phytochemical screening,Antioxidant activity, Silver nanoparticles, FTIR spectroscopy, Antibacterial activity.